DEVELOPMENT OF PHYSIC MAGAZINE AS AN ALTERNATIVE ISLAMIC CHARACTER SELF-LEARNING RESOURCE FOR GROWING SPIRITUAL ATTITUDE AND LEARNING MOTIVATION FOR STUDENTS GRADE XI SMA NEGERI 1 BANTUL - MUSTIKARINI PUDYASWARA; MUNDILARTO MUNDILARTO (Jurnal Pendidikan Fisika, 2016)
The research was aimed to : 1) producting Islamic Physics Magazine which was worthy to be an alternative self-learning resource in chapter dinamic fluid; 2) knowing the achievements of spiritual attitude growth for Senior High School students; and 3) knowing the achievements of learning motivation growth for Senior High School students via Islamic Physics Magazine. The research used developmental research methode which was used 4D models (Define, Design, Development, Dissemination). Define phase was the first phase of developmental Islamic Physics Magazine learning resource based on the curriculum and learning needs via observation in school subject. Design phase was phase that designed Islamic Physics Magazine and data collecting instruments. In develope phase was done a validation product by expert validator and practition validator, first trial, revision of first trial, second trial, and revision of second trial. The trial was done at SMA Negeri 1 Bantul. The research subject were students of XI MIA 5 and students of XI MIA 7 SMA Negeri 1 Bantul that each of the class consist of 26 students. All of data research were collected using questionaires. The kind of the data collected were qualitative data which was suggestions/comments from validator and student’s responses about media, and the quantitative data which was validator’s score, students’responses score, achievement of spiritual attitude score, and achievement of learning motivation score.The result of the developmental research showed that the product, the Islamic Phisics Magazine, was worthy to develope for alternative of self-learning resource. The worthness was get from the valdation result by two validator that assessed “very good” category to all component. Beside of the result validation, the worthness was2Jurnal Pendidikan Matematika dan Sains Edisi ... Tahun ..ke.. 20...also get from students’ respon that assessed “good” category. The result of achievements of spiritual attitude was 4,35 score on the first trial and 4,57 score on the second trial that both of it were in “very good” categories. The learning motivation growth was 3,85 skor that was in “good” at the 1st trial and was 4,27 skor a the second trial that was in “very good” category. Dissemination phase was just done at the school subject by the phisics teacher and giving product to the school library.Keywords : Islamic Physics Magazine, Dinamic Fluid, Spiriual Attitude, Learning Motivation